A Comparison of the Nomological Networks Associated With Forced-Choice and Likert Formats of the Narcissistic Personality Inventory. Issue 3 (4th May 2018) - Miller, Joshua D.; Gentile, Brittany; Carter, Nathan T.; Crowe, Michael; Hoffman, Brian J.; Campbell, W. Keith
ABSTRACT: The Narcissistic Personality Inventory (NPI) is one of the most popular measures of narcissism. However, its use of a forced-choice response set might negatively affect some of its psychometric properties. The purpose of this research was to compare a Likert version of the NPI, in which only the narcissistic response of each pair was given, to the original NPI, in 3 samples of participants ( N = 1, 109). To this end, we compared the nomological networks of the forced-choice and Likert formats of the NPI in relation to alternative measures of narcissism, narcissistic personality disorder, entitlement, self-esteem, general personality traits (reported by self and informants), interpersonal styles, and general pathological traits included in the DSM–5 . The Likert format NPI—total and subscales—manifested similar construct validity to the original forced-choice format across all criteria with only minor differences that seem to be due mainly to the increased reliability and variability found in the Likert NPI Entitlement/Exploitativeness subscale. These results provide evidence that a version of the NPI that employs a Likert format can justifiably be used in place of the original.